2001
DOI: 10.1152/jn.2001.85.1.435
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Cardiorespiratory Networks Revealed by Transsynaptic Virus Expressing GFP

Abstract: A fluorescent transneuronal marker capable of labeling individual neurons in a central network while maintaining their normal physiology would permit functional studies of neurons within entire networks responsible for complex behaviors such as cardiorespiratory reflexes. The Bartha strain of pseudorabies virus (PRV), an attenuated swine alpha herpesvirus, can be used as a transsynaptic marker of neural circuits. Bartha PRV invades neuronal networks in the CNS through peripherally projecting axons, replicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
7
41
1
Order By: Relevance
“…There are number of studies that have employed PRV-152 to demonstrate electrophysiological properties of specific neuronal populations (Derbenev et al 2004(Derbenev et al , 2010Gao et al 2012;Glatzer and Smith 2005;Irnaten et al 2001;. Whole cell recordings from cardiac vagal neurons in the nucleus ambiguus labeled with PRV-Bartha or rhodamine revealed that the electrophysiological properties of the virusand rhodamine-labeled neurons were indistinguishable from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are number of studies that have employed PRV-152 to demonstrate electrophysiological properties of specific neuronal populations (Derbenev et al 2004(Derbenev et al , 2010Gao et al 2012;Glatzer and Smith 2005;Irnaten et al 2001;. Whole cell recordings from cardiac vagal neurons in the nucleus ambiguus labeled with PRV-Bartha or rhodamine revealed that the electrophysiological properties of the virusand rhodamine-labeled neurons were indistinguishable from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell recordings from cardiac vagal neurons in the nucleus ambiguus labeled with PRV-Bartha or rhodamine revealed that the electrophysiological properties of the virusand rhodamine-labeled neurons were indistinguishable from each other. Furthermore, the baroreflex pathway controlling the heart rate was functionally unaltered (Irnaten et al 2001). These observations indicate that the PRV infection does not alter neuronal function, at least at this time period.…”
Section: Discussionmentioning
confidence: 99%
“…This nicotinic facilitation of inhibitory synaptic inputs to cardioinhibitory vagal neurons may be one mechanism for the increased heart rate prevalent in smokers. The nicotinic augmentation of inhibitory neurotransmission to cardiac vagal neurons may also be involved in the respiratory modulation of heart rate, since one cholinergic input to cardiac vagal neurons originates from neurons active in respiration (Irnaten et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Infection with EGFP-expressing PRV-Bartha recombinants allows visualization of live infected neurons by fluorescence without any fixative staining. Recent studies have gone beyond the mere tracing of neuronal circuits to actually record the electrophysiological properties of infected neurons from live brain slices or retinal tissue of infected animals (98,151,188,371,422). The attenuated phenotype of the PRV strain used means reduced cytopathic effects and more physiologically intact neurons.…”
Section: Recent Advances In Viral Tracing Techniquesmentioning
confidence: 99%